Thermoelectric Characterization of Electronic Properties of GaMnAs Nanowires. (17th September 2012) - Wu, Phillip M.; Paschoal, Waldomiro; Kumar, Sandeep; Borschel, Christian; Ronning, Carsten; Canali, Carlo M.; Samuelson, Lars; Pettersson, Håkan; Linke, Heiner
Abstract : Nanowires with magnetic doping centers are an exciting candidate for the study of spin physics and proof-of-principle spintronics devices. The required heavy doping can be expected to have a significant impact on the nanowires' electron transport properties. Here, we use thermopower and conductance measurements for transport characterization of Ga0.95 Mn0.05 As nanowires over a broad temperature range. We determine the carrier type (holes) and concentration and find a sharp increase of the thermopower below temperatures of 120 K that can be qualitatively described by a hopping conduction model. However, the unusually large thermopower suggests that additional mechanisms must be considered as well.